PRIORITIES OF TAX POLICY WITHIN THE FRAMEWORK OF THE “ UZBEKISTAN-2030” STRATEGY: MACROECONOMIC STABILITY AND PROSPECTS OF DIGITAL TRANSFORMATION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article is devoted to the study of the theoretical and practical aspects of the reforms being implemented in the country's tax policy within the framework of the priority goals of the " Uzbekistan - 2030" strategy.